UK burden of injuries study. (1st March 2011) - Lyons, R A; Kendrick, D; Towner, E L; Christie, N; Phillips, C J; Coupland, C; Hayes, M; Macey, S; Brophy, S; Carter, B; Groom, L; Mulvaney, C; et al.
Abstract : Objectives: The UKBOI study was designed to quantify important components of the population burden of injury in the UK. Methods: A mixed methods study, incorporating a multi-centred prospective cohort of injured individuals; extrapolation of patient reported outcomes to population metrics using routine data from emergency departments (ED), hospital discharge registers and mortality data; calculation of Disability Adjusted Life Years (DALYs) using Global Burden of Diseases methodology and estimated indirect costs; and the calculation of direct medical costs. Results: The study recruited 1517 injured individuals. Estimated numbers (and rates per 100 000) for UK population extrapolations were 750 999 (1240) for hospital admissions, 7 982 947 (13 339) for emergency department attendances and 22, 185 (36.8) for injury related deaths, in the financial year 2005/6. An estimated 1 771 486 DALYs were lost from injuries occurring in that year, with 82% due to Years Lived with Disability (YLDs) and 18% from Years of Life Lost (YLLs). Some 20% of DALYs lost were due to YLDs occurring within 12 months post injury and 62% due to lifelong injuries. Direct medical costs were estimated at 482 million for ED visits and 2.15 billion for inpatient stays, with indirect costs of up to 35.5 billion. The qualitative study with 90 participants revealed many additional negative consequences for individuals, family and society. Implications: The high population burden and costs associated with injuries in the UK demonstrates the need for sustained policies and interventions in support of prevention.